Three horizons of technical skills in artificial intelligence for the sustainability of insurance companies - Julio César Acosta-Prado; Carlos Guillermo Hernández-Cenzano; Carlos David Villalta-Herrera; Eloy Wilfredo Barahona-Silva (Administrative Sciences, 2024)
Insurance companies are experiencing unprecedented growth due to several emerging technology functionalities that have transformed the industry's operations. Through the Three Horizons framework, this study explores the technical skills required to use artificial intelligence (AI) for the sustainability of insurance companies. Methodologically, it was carried out in two stages: First, defining the state-of-the-art, which included analysis of the current situation and studying technological surveillance. Second, technical skills and their strategic prevalence were identified for the design of each horizon. As a result, the adoption of AI in insurance companies allows them to transform their personal and data-intensive processes into engines of efficiency and knowledge, redefining the way companies in the sector offer their services. This study identifies the immediate benefits of AI in insurance companies. It provides a strategic framework for future innovation, emphasizing the importance of developing AI competencies to ensure long-term sustainability.
Keywords: 350; artificial intelligence; insurance companies; sustainability; technical skills; three horizon framework